2014
DOI: 10.1007/s12032-014-0099-0
|View full text |Cite
|
Sign up to set email alerts
|

LMO1 is a novel oncogene in lung cancer, and its overexpression is a new predictive marker for anti-EGFR therapy

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer mortality in the world. We report that one oncogene amplified on chromosome 3q26, LMO1, a master transcriptional regulator of stemness, operates to drive strong growth phenotype in NSCLC. We first validate gene expression changes of LMO genes by real-time quantitative RT-PCR real-time quantitative reverse transcriptase-polymerase chain reaction analysis and immunohistochemistry, and we identified gene overexpression of LMO1 compared with non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…[51][52][53] Therefore, targets of Ezh2 other than Hmga2 may play a greater role in fibrosis in this context. RNA-seq also revealed that an Ezh2 deletion and overexpression of Hmga2 share deregulated oncogenic targets such as Lmo1 [54][55][56] in the presence of JAK2V617F. These observations give rise to the hypothesis that when the loss of Ezh2 and/or MIRlet-7 block the inhibition of some oncogenes, Hmga2 may synergistically accelerate such upregulation in the MPN stem cells.…”
Section: V617fmentioning
confidence: 87%
“…[51][52][53] Therefore, targets of Ezh2 other than Hmga2 may play a greater role in fibrosis in this context. RNA-seq also revealed that an Ezh2 deletion and overexpression of Hmga2 share deregulated oncogenic targets such as Lmo1 [54][55][56] in the presence of JAK2V617F. These observations give rise to the hypothesis that when the loss of Ezh2 and/or MIRlet-7 block the inhibition of some oncogenes, Hmga2 may synergistically accelerate such upregulation in the MPN stem cells.…”
Section: V617fmentioning
confidence: 87%
“…Apart from neuroblastoma, the LMO1 gene polymorphisms were also associated with acute lymphoblastic leukemia susceptibility [31]. Additionally, recent studies indicated that in the anti-EGFR therapy, overexpression of LMO1 may be a predictive marker for the colorectal cancer [32], lung cancer [33], and prostate cancer [34]. …”
Section: Discussionmentioning
confidence: 99%
“…LMO1 is one of the novel genes which has been reported in recent studies that is associated with a variety of malignancies such as leukemia, colorectal cancer and lung cancer in terms of tumor progression, metastasis and apoptosis ( 8 , 14 , 15 ). However, only a few studies focused on the relation between LMO1 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%